Follow-up study of musculoskeletal disorders 20 months after the introduction of a mouse-based computer system - Arvidsson, Inger; Axmon, Anna; Skerfving, Staffan (Scandinavian Journal of Work, Environment & Health, 2008)
' ' OBJECTIVES ': 'This study attempted to determine whether musculoskeletal health is influenced by mouse-intensive computer work. ' ' METHODS ': 'The neck–upper limbs of 148 air-traffic controllers (71 women, 77 men) with demanding computer work were examined before (baseline) and a median of 20 months after (follow-up) a change from varied computer work to a mouse-based system, causing a significant change in the physical exposure of the workers (eg, lower variation of work postures and less rest in the forearm extensor muscles, as assessed by technical measurements). Complaints (according to a Nordic questionnaire), diagnoses (standardized physical examination), and psychosocial work environment (Copenhagen Psychosocial Questionnaire) were recorded. ' ' RESULTS ': 'The air traffic controllers had consistently higher prevalences of disorders in the elbows–hands in the follow-up than at the baseline (complaints 30% versus 18%, P=0.03; diagnoses 10% versus 3.4%, P=0.02). The predominance of right-arm disorders was more pronounced in the follow-up than at the baseline. For the neck–shoulders–upper back, there was no consistent difference between the baseline and follow-up values; disorders increased significantly among the “young” controllers (≤37 years), but not among the “older” ones. Perceived decision latitude decreased, while social support increased, but these changes did not explain the disorders that appeared in the elbows–hands. ' ' CONCLUSIONS ': 'Intensive mouse-based computer work, with constrained posture and little rest in the forearm muscles, was associated with an increased risk of disorders in the elbows–hands. This finding should be considered for similar technological developments in other settings.
Keywords: air-traffic control; complaint; computer system; diagnosis; follow-up study; mouse-based computer system; MSD; musculoskeletal disorder; physical examination; prospective study